Pengaruh Bauran Promosi 4C Terhadap Kepuasan Pembelian Online dengan Keputusan Pembelian sebagai Variabel Interverning - Imanda Junifar (Sosio e-Kons, 2021)
This study aimed to determine the direct and indirect effects of the consumer marketing mix, the price of goods, convenience, and communication contained in the Shopee application. An exploratory quantitative survey method was used in this study. The results show that consumers have a significant effect on purchasing decisions and consumer satisfaction. Price has a significant effect on purchasing decisions and consumer satisfaction. Convenience has a significant effect on consumer satisfaction. However, it has no significant effect on purchasing decisions. The promotion has no effect on consumer satisfaction but has a significant effect on purchasing decisions.